Morbid obesity and mental health of women - Rakhimberdyevich, Orazov Mekan; Borisovich, Elagin Ilia; Saulovich, Harnas Sergey; Borisovna, Khamoshina Marina; Ravilevna, Toktar Lilia; Eugenevich, Orekhov Roman; Alexandrovitch, Semenov Pavel (International Journal of Psychosocial Rehabilitation, 2020)
In a study of a different degree of evidence, the mental status of 487 morbidly obese patients was analyzed. It turned out that patients of especially young age more often had a high risk of developing depression. The study clearly established a strong proportional correlation between weight loss and a decrease in depression severity [8].